The Judicial Review Function of Constitutional Courts: A Comparative Study of Indonesia, the United States, and Austria - Abdul Azis, Fouza Azwir; Leviza, Jelly (Jurisprudensi: Jurnal Ilmu Syariah, Perundang-Undangan dan Ekonomi Islam, 2025)
Ideally, the judicial review of regulations by the Constitutional Court aims to ensure the conformity of regulations with the constitution and protect human rights. The Constitutional Court has the authority to test the constitutionality of regulations, but in practice, there are challenges such as procedural complexity and institutional independence. This study aims to compare the function of judicial review by the Constitutional Court in Indonesia, the United States, and Austria. This article is classified as a literature review using a normative legal study approach. The methodology employed is a comparative study. The research results show that although all three countries have regulatory review bodies, there are differences in the process and structure of the institutions. The Indonesian Constitutional Court has a broad role, while the U.S. Supreme Court focuses on specific regulations, and in Austria, the review is conducted by a specialized court with a narrower focus.